A Timeless Link Between Circadian Patterns and Disease. Issue 1 (January 2016) - Mazzoccoli, Gianluigi; Laukkanen, Mikko O.; Vinciguerra, Manlio; Colangelo, Tommaso; Colantuoni, Vittorio
Abstract : The Timeless ( Tim ) gene, originally identified in Drosophila melanogaster and subsequently in mammals, is involved in the molecular clockwork that drives 24 h periodicity in physiology and behavior. The Tim protein is involved not only in circadian rhythmicity but also in embryonic development, cell cycle progression, DNA replication, and the DNA damage response (DDR). It is thus a multifaceted factor implicated in the maintenance of many cellular processes, tissue functions, and ultimately homeostasis of various organisms, from insects to humans. This review highlights the current knowledge of Tim functions, especially the most recent achievements, and illustrates the possible roles that this factor plays in the physiological preservation of health, as well as in the pathogenic mechanisms of related diseases. Trends: The Timeless ( Tim ) gene is evolutionarily conserved from insects to mammals. The Drosophila melanogaster Tim gene is involved in circadian rhythmicity, but the role mammalian Tim plays in this process is still debated. Tim, however, has been implicated in additional and distinct cellular processes comprising DNA replication and the DDR, telomere length and integrity maintenance, as well as cell cycle progression. The precise mechanisms of action of Tim in these processes, or Tim interactions with various protein partners, however, have not been completely elucidated. Tim plays a role in embryonic development and developmental apoptosis, suggesting a potential involvement in mechanisms of tissue regeneration, which could be exploited in translational research and regenerative medicine. Owing to the wide range of functions, Tim has drawn attention for its possible involvement in the pathogenesis of diverse diseases ranging from tumors to psychiatric conditions hallmarked by genetic mutations, alterations of circadian rhythmicity, and other so far unidentified events. Thus, Tim may well represent a therapeutic target in such conditions.